EFFECT OF STEEL PLATES ON SHEAR STRENGTH OF WIDE REINFORCED CONCRETE BEAMS - M. Ibrahim, Amer; D. Salman, Wissam; W. Ahmed, Qusay (Journal of Engineering and Sustainable Development, 2015)
In this study, shear behavior of reinforced concrete wide beams was investigated experimentally. The experimental program consisted of four wide beams of 45 MPa concrete compressive strength tested with a shear span-depth ratio (a/d) equal to 4.52. One of the tested wide beams had web reinforcement as a control specimen, and the other three specimens had no transverse reinforcement but contained vertical shear steel plates. The flexure mode of failure was secured for all of the specimens to allow for shear mode of failure. The key parameters covered in this investigation were the effect of the existence solid and hollow vertical steel plates on the shear capacity of the tested wide beams. The study shows that the contribution of vertical steel plates to the shear capacity was significant and directly proportional to the existence and direction of the steel plates. The increase in the shear capacity ranged from 9.52% to 47.62% for the range of the tested beams compared with the control beam. Transverse vertical steel plates with voids were more effective in the contribution of the shear strength of wide beams and enhances the ductility of the wide beams.